DRY EYE SYNDROME PADA PEKERJA KANTOR: TINJAUAN PUSTAKA - Tyaradhia Ranita Eltidar; Winda Trijayanthi Utama (Medula, 2026)
An epidemiological study in the United States involving 75,000 adults reported that 5,051 individuals, or 6.73%, were diagnosed with Dry Eye Syndrome (DES), highlighting its growing importance as a public health issue, particularly among office workers with prolonged digital screen exposure. The extensive use of computers, smartphones, and tablets contributes to DES primarily through reduced blink frequency and incomplete blinking, which increase tear evaporation and lead to ocular surface dryness. Prolonged screen exposure may also induce oxidative stress and inflammation on the ocular surface, accelerating DES development. Workplace environmental factors, including air conditioning, artificial lighting, and low humidity, further elevate the risk, while blue light from screens may disrupt circadian rhythms, reduce tear production, and exacerbate symptoms. Poor ergonomic practices, such as improper screen positioning and prolonged near work, add visual strain and worsen Digital Eye Strain. A cross-sectional study in Bangladesh in 2023 found that daily screen time exceeding 8 hours, blink rates below 10 blinks per minute, and air-conditioned work environments significantly increased DES risk among office workers. Similar findings were reported in a 2024 cross-sectional study from India, which also identified screen distances of less than 50 cm and workplace humidity below 30% as risk factors. In addition, a cohort study in the Netherlands showed that professionals in legal, health, business, and administrative sectors had a higher risk of developing DES, which has been shown to reduce work productivity after symptom onset.